Ownership and market entry mode choices of emerging country multinationals in a transition country: Evidence from Turkish multinationals in Romania - (:unkn) unknown (Rainer Hampp Verlag, 2014)
Drawing upon key arguments of prevailing theoretical perspectives in international business, this study aims to explain the ownership and market entry strategies of emerging country multinational enterprises (MNE) in a transition country. To this end, the Turkish MNEs’ ownership (joint venture versus wholly owned subsidiary) and entry mode (greenfield versus acquisition) choices for their affiliates in Romania are essentially investigated based on a number of selected case studies. Using qualitative data from semi-structured interviews, this study indicates that a single perspective alone cannot adequately explain the Turkish MNEs’ ownership and entry mode strategies for their affiliates in Romania. © Rainer Hampp Verlag.
Keywords: Emerging countries; Entry mode; Foreign direct investment; Ownership mode; Romania; Turkey